Trends in Mortality from Stroke in Latin America and the Caribbean, 1979-2015 - Vanegas-Lopez, J (Ubiquity Press, 2022)
Background: Stroke is the second largest single cause of death and disability in Latin America and the Caribbean (LAC). There have been large overall declines in stroke mortality rates in most LAC countries in recent decades. Objective: To analyze trends in mortality caused by stroke in LAC countries in the period 1979-2015. Methods: We extracted data for age-standardized stroke mortality rates per 100,000 in LAC for the period 1979-2015 from the World Health Organization Mortality Database. Joinpoint regression was used to analyze the trends and compute the annual percent change (APC) in LAC as a whole and by country. Analyses were conducted by gender, region and World Bank income classification. Results: Mortality from stroke has decreased in LAC over the study period by an average APC of -1.9%. Most countries showed significant downward trends, with the sharpest decreases in Chile, Colombia and Uruguay. We recorded statistically significant decreases of -1.4% and -2.4% in mortality rates in men and women, respectively, in the whole LAC. Southern and high-income countries showed the steepest decreases. Conclusions: Stroke mortality has decreased in LAC, in both sexes, especially in southern and high-income countries. Our results could serve as a reference for the development of primary prevention and acute management of stroke policies focused on countries with higher mortality. © 2022 Elsevier B.V.. All rights reserved.